Evaluation of a Surgical Navigation System for Localization and Excision of Nonpalpable Lesions in Breast and Axillary Surgery - Kjirsten A. Carlson; Cristina Checka; Kelly K. Hunt; Jennifer Jung; Christian Bridges; Puneet Singh; Ana Refinetti; Tanya Moseley; Frances Perez; Cody Mayo; Nina Tamirisa (The Breast Journal)
Introduction. Elucent Medical has introduced a novel EnVisio™ Surgical Navigation system which uses SmartClips™ that generate a unique electromagnetic signal triangulated in 3 dimensions for real-time navigation. The purpose of this study was to evaluate the efficacy and feasibility of the EnVisio Surgical Navigation system in localizing and excising nonpalpable lesions in breast and axillary surgery. Methods. This pilot study prospectively examined patients undergoing breast and nodal localization using the EnVisio Surgical Navigation system. SmartClips were placed by designated radiologists using ultrasound (US) or mammographic (MMG) guidance. The technical evaluation focused on successful deployment and subsequent excision of all localized lesions including SmartClips and biopsy clips. Results. Eleven patients underwent localization using 27 SmartClips which included bracketed multifocal disease (n = 4) and clipped lymph node (n = 1). The bracketed cases were each localized with 2 SmartClips. Mammography and ultrasound were used (n = 8 and n = 19, respectively) to place the SmartClips. All 27 devices were successfully deployed within 5 mm of the targeted lesion or biopsy clip. All SmartClip devices were identified and retrieved intraoperatively. No patients required a second operation for margin excision. Conclusion. In a limited sample, the EnVisio Surgical Navigation system was a reliable technology for the localization of breast and axillary lesions planned for surgical excision. Further comparative studies are required to evaluate its efficacy in relation to the other existing localization modalities.